MicroRNA: Dynamic Regulators of Macrophage Polarization and Plasticity - Self-Fordham, Jezrom Bokcaerin; Naqvi, Afsar Raza; Uttamani, Juhi Raju; Kulkarni, Varun; Nares, Salvador (Frontiers in Immunology, 2017)
The ability of a healthy immune system to clear the plethora of antigens it encounters incessantly relies on the enormous plasticity displayed by the comprising cell types. Macrophages (MΦs) are crucial member of the mononuclear phagocyte system (MPS) that constantly patrol the peripheral tissues and are actively recruited to the sites of injury and infection. In tissues, infiltrating monocytes replenish MΦ. Under the guidance of the local micro-milieu, MΦ can be activated to acquire specialized functional phenotypes. Similar to T cells, functional polarization of macrophage phenotype viz., inflammatory (M1) and reparative (M2) is proposed. Equipped with diverse toll-like receptors (TLRs), these cells of the innate arm of immunity recognize and phagocytize antigens and secrete cytokines that activate the adaptive arm of the immune system and perform key roles in wound repair. Dysregulation of MΦ plasticity has been associated with various diseases and infection. MicroRNAs (miRNAs) have emerged as critical regulators of transcriptome output. Their importance in maintaining health, and their contribution toward disease, encompasses virtually all aspects of human biology. Our understanding of miRNA-mediated regulation of MΦ plasticity and polarization can be utilized to modulate functional phenotypes to counter their role in the pathogenesis of numerous disease, including cancer, autoimmunity, periodontitis, etc. Here, we provide an overview of current knowledge regarding the role of miRNA in shaping MΦ polarization and plasticity through targeting of various pathways and genes. Identification of miRNA biomarkers of diagnostic/prognostic value and their therapeutic potential by delivery of miRNA mimics or inhibitors to dynamically alter gene expression profiles in vivo is highlighted.